Reassessment of the phylogenetic position of the spiny-scale pricklefish Hispidoberyx ambagiosus (Teleostei: Hispidoberycidae) based on comparative morphology - Kimura, Katsuya (Zootaxa, 2024)
The spiny-scale pricklefish Hispidoberyx ambagiosus Kotlyar, 1981, the sole member of the family Hispidoberycidae, is known from only a few specimens collected from tropical waters of the Indo-West Pacific region. Because its phylogenetic position has not been well investigated, the present study describes the osteology, myology and other morphological features of H. ambagiosus, and reassesses the phylogenetic position of the species, and its relationships with related taxa. Many significant characters, including Tominaga’s organ, were newly discovered in H. ambagiosus and related taxa. Following a phylogenetic analysis of characters in 80 transformation series, three most parsimonious trees were obtained, with H. ambagiosus inferred as forming a monophyletic group together with Barbourisiidae, Cetomimidae, Gibberichthyidae, Rondeletiidae and Stephanoberycidae. Within this clade, H. ambagiosus was inferred as a sister taxon of a clade including the latter three of the aforementioned families. It is considered that H. ambagiosus retains many primitive features, having fewer derived characters than other species in the clade including the six families.